2008
DOI: 10.1128/jcm.02107-07
|View full text |Cite
|
Sign up to set email alerts
|

Novel Loop-Mediated Isothermal Amplification Method for Detection of the JP2 Clone of Aggregatibacter actinomycetemcomitans in Subgingival Plaque

Abstract: We developed a loop-mediated isothermal amplification method that detects the JP2 clone of Aggregatibacter actinomycetemcomitans, which induces aggressive periodontitis in adolescents of North and West African descents. Being independent of special equipment, this specific and sensitive method offers significant advantages for screening of patients on a population basis and in clinical settings.Aggregatibacter (Actinobacillus) actinomycetemcomitans (11) has long been suspected as an etiological factor in perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…The sensitivity for the detection of A. actinomycetemcomitans has increased in recent years as a consequence of a change from traditional cultivation methods, which were mostly used earlier ( Frisken et al ., 1990; Könenen et al , 1992; Kamma et al ., 2000). The DNA‐based methods mostly used today can explain some of the discrepancies in the findings reported in various studies ( Riggio et al ., 1996; Chen & Slots , 1999; Poulsen et al ., 2003; Verner et al ., 2006; Seki et al ., 2008). However, differences in carriage rates, not related to methodology, are found (Table 2).…”
Section: Acquisition Stability and Transmission Of A Actinomycementioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity for the detection of A. actinomycetemcomitans has increased in recent years as a consequence of a change from traditional cultivation methods, which were mostly used earlier ( Frisken et al ., 1990; Könenen et al , 1992; Kamma et al ., 2000). The DNA‐based methods mostly used today can explain some of the discrepancies in the findings reported in various studies ( Riggio et al ., 1996; Chen & Slots , 1999; Poulsen et al ., 2003; Verner et al ., 2006; Seki et al ., 2008). However, differences in carriage rates, not related to methodology, are found (Table 2).…”
Section: Acquisition Stability and Transmission Of A Actinomycementioning
confidence: 99%
“…Some diagnostic tools, such as conventional and real‐time PCR for use in laboratories, are already available ( Brogan et al ., 1994; Poulsen et al ., 2003; Orrù et al ., 2006). Also a loop‐mediated isothermal amplification method for detection of the JP2 clone of A. actinomycetemcomitans in dental plaque samples has been developed ( Seki et al ., 2008). Microbial diagnosis is a necessary prerequisite for preventive purposes as well as for microbiological monitoring during phases of treatment of diseased individuals.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…PCR-based detection of Haemophilus and Aggregatibacter in clinical material has focused mainly on rapid diagnosis of H. influenzae meningitis (158-161), improved detection of H. ducreyi (142), and identification of the virulent clone JP2 of A. actinomycetemcomitans (162,163). PCR has also been utilized for detection of H. influenzae DNA in culture-negative middle ear fluids where prior antibiotic therapy has made culturing inconclusive (164) and for improved microbiological surveillance of bacterial meningitis in parts of the world where laboratory facilities for immediate culturing of cerebrospinal fluid samples are not available (165).…”
Section: Identification By Pcrmentioning
confidence: 99%
“…Seki et al applied the loop-mediated isothermal amplification (LAMP) method for detecting the JP2 clone in subgingival plaque from Moroccan adolescents and found that 48 of 72 samples (66.7%) were JP2 positive [25]. The LAMP technology was very sensitive for the JP2 clone, and the detection limit was 10 genome copies, whereas that with conventional PCR was 100 copies [25,32,33]. These findings are identical to the sensitivity of qPCR, and the detection rate was similar to our result (54.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Since this is time consuming, detection using cultures is not suitable for rapid diagnosis. Molecular genetics techniques, which are relatively rapid, including conventional PCR and other molecular-based techniques, have been used to detect the JP2 clone from subgingival plaque [24,25]. However, these are qualitative methods, and no completely quantitative molecular-based detection technique for the JP2 clone has been reported [26].…”
Section: Introductionmentioning
confidence: 99%